Curriculum in Sweden (Journal of the College of Basic Education, 2024)
The current research aims to study the curricula in Sweden according to the distribution of academic stages in general education. The research reviewed in the board specifications of the geographical location and population density of the State of Sweden and then the researcher provided a description of the stages of study and distribution through all the elements of the curriculum of goals, content, teachers, teaching methods and tests, the researcher reviewed Sweden's experience of the comprehensive school and its history and stages of development in order to benefit from the Swedish experience in education within the public education curricula in Iraq The researcher presented a set of recommendations and proposals at the end of the research.